Leveraging on the parent brand image to build brand extensions: a consumer's perspective on the Clover Tropika brand - Maziriri, Eugine (Journal of Business and Management Review, 2024)
The primary objective of the study was to investigate how brand extensions can leverage on the parent brand image in order to achieve a positive brand extension perception. This was investigated in accordance with specific brand building constructs. The study focused on a consumers’ perspective of the Clover Tropika brand within emerging economic areas. The research was based on a quantitative approach which adopted convenience sampling at Mall intercepts. A total sample of 238 consumers responded to a self-administered questionnaire at Southgate and Maponya Mall which are located in the south west of Johannesburg. All respondents were above the age of 18 and consented to participate in the research by willingly placing their completed questionnaires in the box provided on the day. The data techniques used included Structural Equation Modelling (SEM) which had a core focus on Confirmatory Factor Analysis (CFA) which assisted in confirming the relationships proposed in the conceptual model. SEM also focused on path modelling to determine the causal relations. Nine out of the ten hypotheses proposed had a significant level of p<0.001 proving support for the proposed hypotheses. The research found that there is a significant relationship between brand awareness and brand attitudes, as this hypothesis had the highest path coefficient score. After the research was conducted. It was noted that high recall and recognition of the parent brand, accompanied by favorable attitudes, are key factors in leveraging on the parent brand image to build brand extensions. Moreover, brand extensions need to have high perceived fit in order to leverage extensively on the parent brand image.